Direct comparison of [(11)C] choline and [(18)F] FET PET to detect glioma infiltration: a diagnostic accuracy study in eight patients - Verburg, Niels (EJNMMI Res, 2019)
BACKGROUND: Positron emission tomography (PET) is increasingly used to guide local treatment in glioma. The purpose of this study was a direct comparison of two potential tracers for detecting glioma infiltration, O-(2-[(18)F]-fluoroethyl)-l-tyrosine ([(18)F] FET) and [(11)C] choline. METHODS: Eight consecutive patients with newly diagnosed diffuse glioma underwent dynamic [(11)C] choline and [(18)F] FET PET scans. Preceding craniotomy, multiple stereotactic biopsies were obtained from regions inside and outside PET abnormalities. Biopsies were assessed independently for tumour presence by two neuropathologists. Imaging measurements were derived at the biopsy locations from 10 to 40 min [(11)C] choline and 20–40, 40–60 and 60–90 min [(18)F] FET intervals, as standardized uptake value (SUV) and tumour-to-brain ratio (TBR). Diagnostic accuracies of both tracers were compared using receiver operating characteristic analysis and generalized linear mixed modelling with consensus histopathological assessment as reference. RESULTS: Of the 74 biopsies, 54 (73%) contained tumour. [(11)C] choline SUV and [(18)F] FET SUV and TBR at all intervals were higher in tumour than in normal samples. For [(18)F] FET, the diagnostic accuracy of TBR was higher than that of SUV for intervals 40–60 min (area under the curve: 0.88 versus 0.81, p = 0.026) and 60–90 min (0.90 versus 0.81, p = 0.047). The diagnostic accuracy of [(18)F] FET TBR 60–90 min was higher than that of [(11)C] choline SUV 20–40 min (0.87 versus 0.67, p = 0.005). CONCLUSIONS: [(18)F] FET was more accurate than [(11)C] choline for detecting glioma infiltration. Highest accuracy was found for [(18)F] FET TBR for the interval 60–90 min post-injection. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13550-019-0523-8) contains supplementary material, which is available to authorized users.